Teachers As Researchers: Researchers As Teachers? Towards Successful Educational Research - Nair, Sue (Penerbit Universiti Sains Malaysia, 2007)
The teacher research movement has sought to “... weave a research element into the expertise of teachers” (Nisbet, 2005: 43). Much has been done to achieve this aim. There is a considerable body of research which seeks to demonstrate to practicing and student teachers the value of participating in classroom research (for example, Bailey, 2001). The skills required of a teacher researcher have been enumerated (for example, Kincheloe, 2002), and there is a range of literature available to give practical guidance to teacher researchers (for example, Yates, 2004; Miller, 2005). This paper asks why there is not more evidence of teacher research impacting on practice. To consider this question, a number of relevant areas are examined, for example: social and political contexts; school cultures; and teachers’ perceptions of their roles and personal efficacy. Factors within these areas may affect teachers’ motivation to be involved in research. Practical actions to support teachers in becoming self-questioning, reflective and informed teacher researchers are identified. Inevitably, this development in the teachers’ role impacts on the role of university based researchers and on the relationship between schools and universities.